Effect of irrigation and nutrient management in Indian mustard (Brassica juncea) direct-seeded autumn rice (Oryza sativa) cropping system in Assam - Bollaveni, SK; Das, JC; Sharma, A; Sri, BSSN (Plant Science Today, 2026)
Irrigation and nutrient management play a crucial role in the productivity and economics of agricultural crops, including mustard, an important oilseed and paddy, a staple food crop in many countries worldwide. Irrigation and nutrients are 2 major inputs change the scenario of crop growth, yield and economics in all the crops. The study titled “Effect of irrigation and nutrient management in Indian mustard (Brassica juncea) direct-seeded autumn rice (Oryza sativa) cropping system in Assam” was conducted over 2 consecutive years (2016–2017 and 2017–2018) at Assam Agricultural University, Jorhat, Assam. The experiment was conducted during the rabi season (October–February), followed by the summer season (February–June). The irrigation regime with irrigation water (IW):cumulative pan evaporation (CPE) = 1.60 yielded the highest gross and net returns, as well as the highest benefit-cost ratio, followed by IW:CPE = 1.40, for both crops application of 50 % recommended dose of fertilizers (RDF) (N) + 50 % N through farmyard manure (FYM) + biofertilizers resulted in higher values of gross and net return and B:C ratio in both the mustard and rice crops.